Persepsi dan Tindakan Masyarakat Terhadap Pelaksanaan Program Hutan Rakyat (Studi Kasus Desa Kesetnana, Kecamatan Mollo Selatan, Kabupaten Timor Tengah Selatan) - Yohana Chandrya Inggrid Meo; Ludji Michael Riwu Kaho; Nixon Rammang; Lusia Sulo Marimpan (Wana Lestari, 2026)
Land that is left empty without any utilization will experience degradation, which is a process of decreasing land productivity, both temporary and permanent, and in other definitions it is often referred to as unproductive land or idle land that is left uncultivated and generally overgrown with shrubs. The condition of land in Kesetnana Village is mostly left empty or abandoned so that it is overgrown with shrubs. These problems need to be overcome, one of which is rehabilitating land with the Community Forest program. In the community forest program, to support the success of its development, there needs to be community involvement based on the purpose of obtaining benefits. If the community understands the meaning and purpose of their involvement, it will greatly affect their perception. The purpose of this study was to determine community perceptions and actions towards the implementation of the Community Forest program in Kesetnana Village, South Mollo District, South Central Timor Regency. The sample determination in this study used a census technique with a total sample size of 56 households. The measurement scale used is the Likert scale model. The results showed that the community's perception of the implementation of the community forest program in Kesetnana Village was high, with an overall average value of 28.83 with a category value of 2.62 with a very agreeing attitude. The community believes that the existence of community forests will have a good effect on the land utilized for community forests, which among other things can improve land fertility and increase land productivity. Community actions towards the implementation of the community forest program in Kesetnana Village include land preparation, seeding and planting.